2019
DOI: 10.1177/0146167219841621
|View full text |Cite
|
Sign up to set email alerts
|

Three Decades of Research on Induced Hypocrisy: A Meta-Analysis

Abstract: Induced hypocrisy is a sequential, two-step, cognitive dissonance procedure that prompts individuals to adopt a proattitudinal behavior. The present meta-analysis of 29 published and nine unpublished induced-hypocrisy studies enabled us to test three key dissonance-related issues. First, is hypocrisy effective in promoting change in behavioral intention and behavior? Our analyses supported the idea that hypocrisy (vs. control) increased both behavioral intention and behavior. Second, does hypocrisy generate ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 75 publications
2
41
2
1
Order By: Relevance
“…It might be true that people derive well-being from acting consistently (Donahue et al, 1993; although see Cross et al, 2003;Suh, 2002) or that acting dissonantly in some contexts produces an aversive state (Cooper and Fazio, 1984;A. McGrath, 2017;Zanna & Cooper, 1974; although see Priolo et al, 2019 for a recent, inconclusive meta-analysis). But intrapsychic explanations have difficulty predicting how the social environment moderates these internal states.…”
Section: Is Principled Behavior Psychologically Fulfilling?mentioning
confidence: 99%
See 1 more Smart Citation
“…It might be true that people derive well-being from acting consistently (Donahue et al, 1993; although see Cross et al, 2003;Suh, 2002) or that acting dissonantly in some contexts produces an aversive state (Cooper and Fazio, 1984;A. McGrath, 2017;Zanna & Cooper, 1974; although see Priolo et al, 2019 for a recent, inconclusive meta-analysis). But intrapsychic explanations have difficulty predicting how the social environment moderates these internal states.…”
Section: Is Principled Behavior Psychologically Fulfilling?mentioning
confidence: 99%
“…People are driven to act consistently, so much so that this tendency can be exploited for persuasion and behavioral change (Dickerson et al, 1992;Osbaldiston & Schott, 2012). If they advocate a value, either spontaneously or because they're asked to, and are then reminded of how their behavior diverges from that value, they adjust their behavior to conform (Priolo et al, 2019;Stone & Fernandez, 2008b, 2008a. If they are asked to speak highly of an activity, they are more likely to report liking it later, even if it's boring and monotonous (Festinger & Carlsmith, 1959).…”
Section: Explaining Cognitive Dissonance and Foot-in-the-door Effectsmentioning
confidence: 99%
“…Some recent paradigms have indeed shifted their focus to the manipulation of inconsistency. For instance, the hypocrisy paradigm (Aronson, 1992; Stone and Fernandez, 2008; Priolo et al, 2019) compares inconsistent conditions to neutral or consistent ones. Likewise, some new paradigms focus on minimal inconsistencies, that is, inconsistencies that involve very few cognitions other than the inconsistency per se (e.g., Levy et al, 2017), and compare inconsistent conditions to neutral ones.…”
Section: The Operationalization Issue: Problems and Ways Forwardmentioning
confidence: 99%
“…This standardization of the induction would rely on both a better operational definition of the manipulated variables, as we mentioned above, and also on the report of variables that are likely to influence the CDS, and thus its regulation. For instance, the hypocrisy paradigm has been investigated with very different topics and methods, and Priolo et al (2019) found no evidence in their meta-analysis for the existence of a CDS. This conclusion could question either the theory or either the relevance of the methodology.…”
Section: The Operationalization Issue: Problems and Ways Forwardmentioning
confidence: 99%
“…They designed a sequential procedure to achieve cognitive dissonance, by illustrating the gap between what a person knows he or she should do in a certain situation (socially desired behaviors) and what he or she actually did (transgressions). A recent meta-analysis supports that hypocrisy induction has a moderate positive effect on both behavioral intention and behavior (Priolo et al, 2019).…”
Section: Chaptermentioning
confidence: 95%